2019
DOI: 10.1136/bcr-2019-230633
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented paravenous retinochoroidal atrophy associated with unilateral cystoid macular oedema

Abstract: A 65-year-old man was referred to our department with complaints of blurred vision in the left eye. Funduscopic examination revealed areas of retinochoroidal atrophy along the retinal veins bilaterally and bone spicule pigmentation along the nasal and superior temporal venous branches, as well as macular oedema in the left eye. Fluorescein angiography, visual field test, optical coherence tomography and electrophysiological examination were performed, and results were compatible with the diagnosis of pigmented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…As a consequence, it is difficult to identify this condition in patients. There have been previous reports of PPRCA with strabismus [4], amblyopia [5], nystagmus [5], macular cystoid edema [6], macular hole [7], etc., but its relationship with concomitant diseases has not been reported. Huang et al suggested that PPRCA is an additional, incomplete, self-limiting form of retinitis pigmentosa (RP) [1].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, it is difficult to identify this condition in patients. There have been previous reports of PPRCA with strabismus [4], amblyopia [5], nystagmus [5], macular cystoid edema [6], macular hole [7], etc., but its relationship with concomitant diseases has not been reported. Huang et al suggested that PPRCA is an additional, incomplete, self-limiting form of retinitis pigmentosa (RP) [1].…”
Section: Discussionmentioning
confidence: 99%
“…Only a small number of PPRCA cases with macular involvement have been reported in the literature. 3 , 5 Shona et al 1 reported in a series of 23 cases that two-thirds of the patients were asymptomatic and the most common macular changes were mild or severe disruption of the outer retina and RPE, and/or choroidal thinning. They found mild macular intraretinal cysts in only one patient with extensive PPRCA.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of PPRCA is unknown, but it is believed to be hereditary or associated with an initial inflammatory cause. 1 , 2 , 3 , 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
“…Regarding the use of anti-VEGF agents, studies on peripheral ischemia have so far shown contradictory findings, which mostly depend on the imaging technique employed to measure it. Some authors found no appreciable peripheral CNP improvement with UWF FA in DR patients after anti-VEGF treatment over a follow-up of 3 to 12 months ( 72 74 ). A prospective UWF FA study comparing patients with PDR treated with intravitreal 2.0 mg aflibercept either monthly or quarterly revealed stability in the amount of CNP in patients receiving monthly aflibercept but not in those with lower dosage, leading the authors to hypothesize that the anti-VEGF agents dosage may affect the perfusion status ( 75 ).…”
Section: Management Of Capillary Non-perfusionmentioning
confidence: 99%